A study on the temperature dependence of the threshold switching characteristics of Ge2Sb2Te5 - Lee, Suyoun; Jeong, Doo Seok; Jeong, Jeung-hyun; Zhe, Wu; Park, Young-Wook; Ahn, Hyung-Woo; Cheong, Byung-ki (AMER INST PHYSICS, 2010)
We investigated the temperature dependence of the threshold switching characteristics of a memory-type chalcogenide material, Ge2Sb2Te5. We found that the threshold voltage (V-th) decreased linearly with temperature, implying the existence of a critical conductivity of Ge2Sb2Te5 for its threshold switching. In addition, we investigated the effect of bias voltage and temperature on the delay time (t(del)) of the threshold switching of Ge2Sb2Te5 and described the measured relationship by an analytic expression which we derived based on a physical model where thermally activated hopping is a dominant transport mechanism in the material.
Keywords: PHASE-CHANGE MEMORIES; AMORPHOUS-SEMICONDUCTORS; CHALCOGENIDE GLASSES; THIN-FILMS; MECHANISM